1984
DOI: 10.1093/nar/12.2.1277
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of multimeric tRNA genes

Abstract: We have constructed a set of plasmids carrying a tRNAPro gene from C. elegans in a head to tail dimeric and trimeric arrangement with virtually no spacer sequence. We show that in two different transcriptional systems, each coding region functions as an internal promoter directing the synthesis of independent transcriptional products. This is in contrast with the property of natural head to tail dimeric arrangements found in yeast, where only one coding region functions as promoter (Mao et al., 1980 Cell 20, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…We (11) and others (12) have shown that, as in Drosophila systems (13), homologous in vitro transcription of yeast tRNA genes was dependent, besides the ICRs, on a 5' flanking region the sequence of which varies slightly between position -1 and -10, and can vary somewhat more upstream of position -10. This is in contrast to HoLa or Nucleic Acids Research oocyto systems, whoro any stretch of DNA can function as a 5' flank for tDNA (14). Tho transcriptional stop signal, ,4Ts, is part of the 3'flanking DNA, a rogion that in some systems appears to also influoneo the efficiency of transcription (15).…”
Section: Introductionmentioning
confidence: 94%
“…We (11) and others (12) have shown that, as in Drosophila systems (13), homologous in vitro transcription of yeast tRNA genes was dependent, besides the ICRs, on a 5' flanking region the sequence of which varies slightly between position -1 and -10, and can vary somewhat more upstream of position -10. This is in contrast to HoLa or Nucleic Acids Research oocyto systems, whoro any stretch of DNA can function as a 5' flank for tDNA (14). Tho transcriptional stop signal, ,4Ts, is part of the 3'flanking DNA, a rogion that in some systems appears to also influoneo the efficiency of transcription (15).…”
Section: Introductionmentioning
confidence: 94%